Management of Community Learning Activities Center (CLAC) in District Kotawaringin Timur - Darlan, Muhammad Norsanie (Journal of Nonformal Education, 2017)
The purpose of this study will be to find a solution as follows: (1). Want to know if PKBM Lotus Mekar has a way in efforts to educate the life of the Nation. (2). Want to know how PKBM Eka Bahurui in cooperation with local government. In order for this institution to manage properly. The method in this research, using qualitative approach while the subject of this research is: Community Learning Activity Center (PKBM) in Kotawaringin Timur region. And the subjects in this study, hádala: managers, tutors and residents learn. The data source is the organizer of PKBM organizer and tutor at the non-formal education institution. To obtain data assisted by interview guides, observation and documentation. The results of this study are: (1). PKBM Lotus Mekar has a way in efforts to educate the life of the Nation, by providing various programs for prospective learners (WB) motivated to become learners and able to follow the process of learning well; (2). PKBM Eka Bahurui in performing his duties in cooperation with local government. So, it can manage the institution well. And it turns out the learning process at the time of this research took place no longer use the village office but on the blessing of local government accompanied budget cost so PKBM already has building hermanen